The Effect of Spin Wheel on Students Cognitive Ability in Tajweed Learning - salsabila, Unik hanifah; Ivan, Imam Mars Miasya Ibnu; Novianti, Deti; Pratama, Hendy; utami, Etik Listiani (STAI Serdang Lubuk Pakam, 2023)
The low ability of students at SMK Muhammadiyah 1 Wates in understanding recitation material is the background for this research. Learning media is something that is highlighted because it has an influence on the learning process. Success in learning is influenced by learning media, one of the efforts made to overcome the problem is the use of the spin wheel. This research aims to test the effect of the spin wheel on students' cognitive abilities to understand recitation material. The method used in this research is a quantitative method with a quasi-experiment design approach through time series design calculations. Samples were taken using purposive sampling technique. Data were analyzed using descriptive statistics, t-test and f-test. The validity of the research shows that there is a positive influence of using the spin wheel in learning recitation on students' cognitive abilities, as evidenced by an increase in the average posttest score tested. The results of the t-test show sig 0.000 or <0.05 and the f-test shows fcount 17.031 or > ftable 4.121, which means there is a significant positive influence of using the spin wheel on students' cognitive abilities.